A case series of fatal meningoencephalitis in Mongolia: epidemiological and molecular characteristics of tick-borne encephalitis virus - Uyanga Baasandavga; Burmaajav Badrakh; Natsagdorj Burged; Otgonsuren Davaajav; Tungalag Khurelsukh; Amber Barnes; Unursaikhan Ulaankhuu; Tsogbadrakh Nyamdorj (World Health Organization Regional Office for the Western Pacific, 2019)
In Mongolia, the incidence and fatality rates of tick-borne encephalitis (TBE) have been increasing. We aimed to identify the epidemiological and molecular characteristics of tick-borne encephalitis virus (TBEV) associated with fatal meningoencephalitis in Mongolia. We conducted a descriptive study of 14 fatal cases of TBE that occurred between 2008 and 2017 in Mongolia. Reverse transcription polymerase chain reaction (RT-PCR) was used to detect viral RNA in brain tissue. RT-PCR products from six patients who died from TBE between 2013 and 2017 were directly sequenced and analysed phylogenetically. Ticks collected from Selenge and Bulgan provinces were also tested for TBEV by RT-PCR. Between 2008 and 2017, there were 14 fatal TBE cases in hospitals in Mongolia. The 14 patients who died reported receiving tick bites in Bulgan or Selenge province; 71.4% of deaths resulted from tick bites in Bulgan province. The TBE case fatality rate was 28.6% for patients in Bulgan province and 2.7% for those in Selenge province. All of the fatalities were men; the median age was 45 ± 12.6 years. Tick bites occurred between April and June in forested areas. In 2013, a 388 base pair fragment of the envelope (E) gene was obtained from a hospitalized patient. The closest relatives of this virus are Far-Eastern TBEV isolates. The case fatality rate differed between two provinces where tick bites occurred. A higher number of TBE cases and the virulent Far-Eastern subtype occurred in patients in Bulgan province. This province should increase vaccination coverage, training, education and investigations.